The role of active aging in preventing depressive symptoms in elderly individuals: an integrative review (Research, Society and Development, 2020)
Objectives: To describe the relationship between active aging and the presence of symptoms of depression in elderly patients. Methodology: This is an exploratory, descriptive study, of the type Integrative Literature Review, in which data were collected from the virtual research libraries: Online Electronic Scientific Library (SCIELO), Virtual Health Library (BVS), and Latin Literature American and Caribbean Health Sciences (LILACS). Results: It was found that the participation of the elderly in physical activities appropriate for their age group, and social interaction based on cultural events such as: theaters, cinema, museum, galleries, etc., presented itself as a significant variable for reducing the rate of depression. Conclusion: Active aging is an important factor for improving the quality of life in elderly individuals, making it necessary to develop programs in the family health strategy that provide opportunities for social interaction and physical activity in the elderly.